Melanoma in pregnancy – where we are? - Izycki, Dariusz; Kerrigan, Christopher Patrick; Kazmierczak, Maciej (Menopause Review/Przegląd Menopauzalny, 2013)
With rising rates of melanoma and women bearing children at older ages, the incidence of malignant melanoma in pregnancy will continue to increase. Initial reports in the 1950s portrayed a belief of the medical community that pregnant women who were diagnosed with malignant melanoma suffered a poorer prognosis. Numerous studies since then have shown that this is not the case, and pregnancy has not been shown to have a negative impact on the prognosis of malignant melanoma. Various mechanisms of hormones affecting malignant melanoma have been proposed, although nothing conclusive has been found. And although very rare, fetal metastasis is a serious risk and needs to be kept under consideration. Continual research and period reviews are necessary to best understand any effects of pregnancy on malignant melanoma, guide research, and maximize patient care.